INDUKSI IN VITRO TANAMAN GAHARU (Aquilaria microcarpa Baill.) DARI EKSPLAN TUNAS AKSILAR DENGAN PENAMBAHAN 6-BENZYLAMINOPURINE (BAP) - Suci Riska Wahyuni; Wahyu Lestari; Eka Novriyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Aquilaria microcarpa Baill. can produce agarwood products that can be used for various purposes, therefore it can caus a high demand for the product. Nowadays, these species are being hunted in their natural habitats. It is worried that this plant will be endangered, hence the conservation efforts for Aquilaria is necessary. The method of in vitro propagation of plants is a solution to large seed production in short time. This study aimed to obtain the optimal concentration in inducing in vitro shoots. Induction of shoots from axillar bud explants that cultured in MS medium containing BAP with concentrations of 0.0; 0.1; 0.2; 0.3; 0.4; 0.5 mg/l. The design used was completely randomized design (CRD). The observed parameters included bud appearance time, shoot number and percentage of explants that formed shoots. Data was descriptively analyzed. The results showed that the fastest emerging shoots was obtained at 0.4 mg/l BAP treatment in the third week. The optimal BAP concentration that could trigger the highest number of bud formation 0.4 mg/l BAP that produced three buds with 33.33% of bud formation.